Kontribusi Keterampilan Membaca Pemahaman terhadap Keterampilan Pemecahan Masalah Matematika Kelas V SD Negeri Kecamatan IV Nagari, Kabupaten Sijunjung - Hendriani, Maifit (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
Based on preliminary study in the fifth grade elementary school in IV Nagari district at Sijunjung, problem-solving skills of the mathematics at students is relatively low, from 10 questions of the problem-solving skill that contain in odd semester exam only 43% students can complete it. This research main to describe the comprehension reading skills and problem solving skills math, and contribution comprehension reading skills of the mathematical problem solving skills Elementary School fifth grade students in IV Nagari district, at Sijunjung. This research is a correlational study. The population in this study is a fifth grade students throughout the District IV Nagari, Sijunjung. The sampling technique used random sampling. Instruments for collecting data is comprehension reading skill test, creativity and problem solving skills of mathematics. The analysis technique used descriptive and correlational. The results show: 1) Elementary School fifth grade students in IV Nagari district have high comprehension reading skills is 42.86% and high math problem-solving skills is 50.55%; 2) there is a significant and positive contributiont correlation between reading comprehension skills to the math problem solving skills with a correlation coefficient 0.646